Lauric acid sophorolipid: accelerating the gelation of silk fibroin - Hirlekar, Swarali; Ray, Debes; Aswal, Vinod K.; Prabhune, Asmita A.; Nisal, Anuya (ACS Omega, 2020)
Silk fibroin (SF) hydrogels find wide applications in tissue engineering. However, their scope has been limited due to the long gelation time in ambient conditions. This paper shows the reduction in gelation time of silk fibroin to minutes upon doping with a newly synthesized lauric acid sophorolipid (LASL). LASL comprises a fatty acid, lauric acid (with a 12-carbon aliphatic chain), that is derivatized by glucose molecules using a non-pathogenic yeast Candida bombicola. LASL was characterized using spectroscopic (Fourier transform infrared spectroscopy) and chromatographic (high-performance liquid chromatography, thin-layer chromatography, and high-resolution mass spectrometry) methods. This gelation of SF is comparable to the effect of an anionic surfactant, sodium dodecyl sulfate (SDS). The microstructure of SF-LASL hydrogels was investigated by small-angle neutron scattering (SANS) measurements and exhibited the beads-on-a-necklace model. The rheological properties of these hydrogels show similarity to SF-SDS hydrogels, therefore presenting a greener alternative for tissue engineering applications.